The Influence of Promotion and Consumer Behavior in Increasing Sales Volume at PT Mulia Boga Raya Tbk - Syahrial Helmi putra; Lambok Manurung; Putri Mauliza (CV Edujavare Publishing, 2026)
Amidst the fierce competition in the food and beverage industry, companies must optimize marketing strategies and understand customer actions to sustain business growth. This study addresses how market interventions and customer dynamics drive revenue. This research aims to analyze the partial and simultaneous effects of promotion and consumer behavior on sales volume at PT Mulia Boga Raya Tbk. The method applied is a field study using an associative quantitative approach, which processes statistical data to test hypotheses and determine the relationships between the measured variables. The results indicate that promotion (t-count 2.313 > t-table 1.669, sig 0.024) and consumer behavior (t-count 3.550 > t-table 1.669, sig 0.001) both have significant partial effects on sales. Simultaneously, both factors heavily influence sales volume, as evidenced by the high F-value (F-count 41.658 > F-table 3.138, sig 0.000), which successfully rejects the null hypothesis. It is concluded that promotion and consumer behavior, both individually and collectively, provide a positive and statistically significant contribution to increasing the sales volume at PT Mulia Boga Raya Tbk.